MEDICINAL HERBS USED BY HIV-POSITIVE PEOPLE IN LESOTHO - Mugomeri, Eltony; Chatanga, Peter; Chakane, Ntema (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
BACKGROUND: The use of medicinal herbs whose efficacy and toxicities are not known by HIV-positive people in Lesotho is a threat to the effectiveness of antiretroviral treatment. OBJECTIVES: This study explored some medicinal herbs used by HIV-positive people in Lesotho and the reasons for their use.METHODS: This was a cross sectional study based on a questionnaire distributed to purposively-sampled HIV-positive people in Leribe and Maseru districts of Lesotho. The participants’ socio-demographic and clinical variables were summarized using frequency tables in Stata version 13 statistical software. Data variables for medicinal herbs used, frequency of use, uses by the participants and in the literature, parts of plants used and the method of preparation were also explored.RESULTS: Out of 400 questionnaires distributed to the participants, 389 were returned with data acceptable for analysis. Ages of the participants ranged from 18 to 75 years (Mean=43 + 11.6). Out of the 272 (69.9%) participants who conceded that they had used medicinal herbs at least once, 30 (7.7%) participants used medicinal herbs frequently while 242 (62.2 %) rarely used the herbs. At least 20 plant species belonging to 16 families were reportedly used by the participants. Asteraceae was the most common plant family reportedly used by the participants. Allium sativum and Dicoma anomala, reportedly used by 21.0% and 14.3% respectively, were the most commonly used medicinal herbs in this population. In addition, boosting the immune system and treating gastrointestinal ailments, apparently cited by 32% and 28% participants respectively, were the most commonly reported reasons for using medicinal herbs.CONCLUSION: A considerable proportion (69.9%) of HIV-positive people use medicinal herbs in this population, while 7.7% use them frequently. At least 20 plant species belonging to 16 families were reportedly used by the participants. HIV counselling protocols in Lesotho should emphasize the dangers of using medicinal herbs whose safety and compatibility with antiretroviral drugs is not known. The efficacy and toxicity profiles of the medicinal plants identified in this study need to be investigated. Furthermore, the effects of these plants on antiretroviral treatment outcomes including herb-drug interactions need to be explored.